A Mini Review of Conductive Graphene/ Polymer Composites - , Victor K. Samoei, Ahalapitiya H. Jayatissa (Archives of Current Research International, 2025)
Conductive polymer–graphene composites have emerged as a promising class of materials with exceptional electrical, mechanical, and thermal properties, making them highly suitable for applications in flexible electronics, energy storage, and biomedical devices. The unique combination of \(π\) - \(π\) interactions and strong interfacial bonding between graphene and conductive polymers enhances charge transport, mechanical strength, and environmental stability. This review provides a comprehensive analysis of recent advancements in the synthesis, processing techniques, and structure-property relationships of these composites. Key focus areas include the role of graphene functionalization, polymer matrix selection, dispersion strategies, and the influence of composite morphology on electrical conductivity. Additionally, we discuss their applications in supercapacitors, sensors, electromagnetic shielding, and next-generation electronic devices. Finally, challenges related to scalability, stability, and fabrication techniques are addressed, along with future perspectives on optimizing these materials for industrial applications.